Safety evaluation of food enzyme trypsin from porcine pancreas - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) (EFSA Journal, 2021)
Abstract The food enzyme trypsin (EC 3.4.21.4) is extracted from porcine pancreas by Novozymes A/S. The food enzyme is intended to be used for hydrolysis of whey proteins employed as ingredients in infant formulae, follow‐on formulae and in food for special medical purposes. Based on maximum use levels and the maximum permitted protein content in infant formula, dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be 32 mg TOS/kg body weight (bw) per day for infants. The Panel considered that this value covers all population groups consuming these formulae. In the toxicological evaluation, clinical studies with pancreatic enzymes were considered. Hypersensitivity to the pharmaceuticals was identified as the major side effect. However, allergic reactions to porcine pancreatic enzymes in hydrolysed foods have not been reported. The Panel considered that a risk of allergic sensitisation to this food enzyme after consumption of products prepared by hydrolysis of milk could not be excluded in infants but considered the likelihood to be low. Based on the origin of the food enzyme from edible parts of animals, the data provided by the applicant and supported by the evaluation of clinical studies based on pancreatic enzymes and the estimated dietary exposure, the Panel concluded that the trypsin from porcine pancreas does not give rise to safety concern under the intended conditions of use.